Diagnóstico da acessibilidade informacional na biblioteconomia brasileira - Fernandes, Joana D'Arc Páscoa Bezerra (2018)
The hugh advance in science and technology, that converges to the unfolding of other subareas and specializations of knowledge, together with the production and sharing of content in digital medium of fast, free and democratic form, has as one major consequence the phenomenon of the informational superabundance that is observed in modern society. Two areas are in evidence in this scenario, first the librarianship role as the area of knowledge responsible for the technical treatment, organization and dissemination of information; and second the Information Science as an area that has the information and the phenomena that permeate it as an object of study is highlighted. It also highlights the existence of a wide range of technological resources created to enable access to information. However there are some minority groups of people on the margins of these possibilities, for whom access to information is still very difficult and in some cases even impossible for they. It is believed that information accessibility is an important tool for social inclusion and therefore must be understood and studied. In view of this finding, the objective was to make a diagnosis of information accessibility in the Brazilian librarianship in order to know the perception of the area and its contribution to solve the problem. For this, a bibliographical research was carried out, where the theoretical and epistemological inputs were obtained, and the basis for the analysis of technical library processing as a tool for informational accessibility; followed by an exploratory research where the theoretical results were confronted with the librarian practice; and an explanatory research where librarians from all Brazilian states were consulted about the understanding of the subject and its problematics, academic formation and professional performance. The results obtained from the analysis of the data revealed that although there is an interest of the area by the theme and an initial effort, there is still much to be done for the effective reach of the informational accessibility.